2012
DOI: 10.3402/ijch.v71i0.18412
|View full text |Cite
|
Sign up to set email alerts
|

Community-based Participatory Process – Climate Change and Health Adaptation Program for Northern First Nations and Inuit in Canada

Abstract: ObjectivesHealth Canada's Program for Climate Change and Health Adaptation in Northern First Nation and Inuit Communities is unique among Canadian federal programs in that it enables community-based participatory research by northern communities.Study designThe program was designed to build capacity by funding communities to conduct their own research in cooperation with Aboriginal associations, academics, and governments; that way, communities could develop health-related adaptation plans and communication ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 5 publications
1
27
1
1
Order By: Relevance
“…Aligning with our inclusion criteria, 89% of the examined literature had water as its main focus. Our review confirmed that the research to date has predominantly focused on water in the context of drinking water (26%); those that did not, instead used water as an example of how Indigenous knowledge, ideas, and practices are applied to water and used in other environmental contexts (see Jones, Rigg, & Lee, 2010;King, 2004;Peace & Myers, 2012;Riedlinger & Berkes, 2001).…”
Section: Context and Scope Of Included Articlessupporting
confidence: 74%
See 2 more Smart Citations
“…Aligning with our inclusion criteria, 89% of the examined literature had water as its main focus. Our review confirmed that the research to date has predominantly focused on water in the context of drinking water (26%); those that did not, instead used water as an example of how Indigenous knowledge, ideas, and practices are applied to water and used in other environmental contexts (see Jones, Rigg, & Lee, 2010;King, 2004;Peace & Myers, 2012;Riedlinger & Berkes, 2001).…”
Section: Context and Scope Of Included Articlessupporting
confidence: 74%
“…This literature documented Indigenous relationships to water and/or lands, oral histories, and traditional knowledge. Interestingly, these articles also tended to be published more recently; two-thirds of articles in this category were published after 2010 (Anderson, Chow, & Haworth-Brockman, 2011;Baird et al, 2013;Caine, 2013;Fresque-Baxter, 2013;Grimwood & Doubleday, 2013;Longboat, 2012;McGregor, 2012;Peace & Myers, 2012;Restoule et al, 2013;Sam, 2013;Szach, 2013). Three articles specifically explored the perspectives of women and their relationship with land and water (Anderson, 2008;McGregor, 2011;Szach, 2013) and one focused on youth (Fresque-Baxter, 2013).…”
Section: What the Research States As Its Purpose And Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of articles mentioned climate change as justification for pursuing CBM, a limited number of articles (n=8) described the implementation/evaluation of a community-based food security monitoring system including climate change indicators. The studies that did consider climate change were mostly situated in Arctic regions [71,[75][76][77][78]; for example, a study in Alaska employed a participatory CBM system to explore environmental conditions likely associated with climate change, health, and food security outcomes [76]. In another study, an integrated CBM system in Nunavik, Canada tracked climatic and ice conditions to support safe access to land and other resources [71].…”
Section: More Articles Focused On Men's Participation In Monitoringmentioning
confidence: 99%
“…In this context, research on human dimensions of climate change in the Canadian North has seen increasingly meaningful partnerships with and leadership by Inuit communities. Such research uses diverse approaches premised on active community participation through all stages of the research process (Harper et al, 2012;Pearce et al, 2012;McClymont Peace and Myers, 2012). These approaches include PhotoVoice (Healey et al, 2011) and digital storytelling (Cunsolo Willox et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%